(untitled) (Journal Genta Kebidanan, 2024)
Childbirth is the event of the birth of a baby, the placenta and amniotic membranes come out of the mother’s uterus. Every delivery is at risk of experiencing labor complications that have an impact on the occurrence of maternal and fetal death. One such complication is prolonged labor. There are several efforts that can be made to prevent prolonged labor, one of which is the birthing ball. The purpose of this study was to determine the effect of the birthing ball on labor pain during the first active phase in mothers giving birth in the working area of the Public Health Center I of East Denpasar District. The design used in this study was a quasy experiment with a two-group-only post-test design. The sample in this study was 30 respondents with a purposive technique. The results showed that all respondents (100%) in the control group stated that the labor pain scale of the First Stage of the Active Phase was severe and all respondents (100%) in the control group experienced a decrease in the pain scale to moderate. Based on the results of the Mann-Whitney analysis, Asymp. Sig. (2-tailed) = 0.000 <0.05 which means there is an effect of the birthing ball intervention on the scale of labor pain in the active phase of the first stage.